R E V I E W: In Vitro Selection and Somaclonal Variation for Biotic and Abiotic Stress Tolerance - ENDANG GATI LESTARI (Biodiversitas Journal of Biological Diversity, 2006)
As an alternative technology, plant improvement through somaclonal variation is expected to support conventional breeding. New superior variants with a better performance and more attractive texture could be obtained through this method. To enhance genetic variation, both physical and chemical treatments such as gamma ray (Co60) and Ethyl Methane Sulphonate (EMS) compound could be applied. In particular for vegetative propagated plants, in vitro induced mutation is the most effective method to improve variation. For obtaining the desired characteristic of plant, in vitro selection is the best method due to its capability to manipulate the variation to the expected result. Therefore, by applying the selection agent to the media, plant tolerance to both abiotic and biotic could be acquired. Generally, the tolerance at the callus level at the specific selection agent is positively correlated with the tolerance at the plant level. At this point, PEG (polyethylene glycol) and manitol is chemical compound useful for drought tolerance, fusaric or filtrate is for fusarium wilt, A1Cl3.6H2O is for Al tolerance. Â© 2006 Jurusan Biologi FMIPA UNS Surakarta Key words: somaclonal variation, in vitro selection, induced mutation.